2018
DOI: 10.1155/2018/5906819
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling Suggests Extensive Metabolic Rewiring of Human and Mouse Macrophages during Early Interferon Alpha Responses

Abstract: Emerging evidence suggests that cellular metabolism plays a critical role in regulating immune activation. Alterations in energy and lipid and amino acid metabolism have been shown to contribute to type I interferon (IFN) responses in macrophages, but the relationship between metabolic reprogramming and the establishment of early antiviral function remains poorly defined. Here, we used transcriptional profiling datasets to develop global metabolic signatures associated with early IFN-α responses in two primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 107 publications
2
10
1
Order By: Relevance
“…2, and Fig. 3;Ahmed et al, 2018;Boshuizen et al, 2016;Li et al, 2011a;Pulliam et al, 2014). Elevated scavenger receptors class A expression can also be found in human peripheral blood mononuclear cells (PBMCs) from subjects with elevated IFN signatures, such as SLE patients and HIV-infected individuals (Table 1 and Fig.…”
Section: Type-i Ifn-associated Cells In Atherogenesismentioning
confidence: 96%
See 1 more Smart Citation
“…2, and Fig. 3;Ahmed et al, 2018;Boshuizen et al, 2016;Li et al, 2011a;Pulliam et al, 2014). Elevated scavenger receptors class A expression can also be found in human peripheral blood mononuclear cells (PBMCs) from subjects with elevated IFN signatures, such as SLE patients and HIV-infected individuals (Table 1 and Fig.…”
Section: Type-i Ifn-associated Cells In Atherogenesismentioning
confidence: 96%
“…Type-I IFNs have been shown to suppress both mouse and human macrophages' inflammatory cytokine production and inflammasome activity through antiinflammatory cytokine induction, such as IL-10, epigenetic regulation affecting chromatin accessibility, and metabolic rewiring, for instance, oxysterol 25-hydroxycholesterol production (Table 1 and Fig. 3; Ahmed et al, 2018;Cheng et al, 2019;Guarda et al, 2011;Reboldi et al, 2014). By contrast, upon type-I IFN stimulation, human peripheral monocyte-derived macrophages (MDMs) restore their inflammatory function silenced by TNF-induced LPS tolerance through reprogramming the accessibility of NF-κB-associated chromatin regions (Table 1; Park et al, 2017).…”
Section: Type-i Ifn-associated Cells In Atherogenesismentioning
confidence: 99%
“…The mouse studies were particularly informative because IFNα exposure was regulated. Although it has been demonstrated that type I IFN stimulation can increase OXPHOS and FAO in DCs and MCs 36 , 38 , inhibit isocitrate dehydrogenase (part of the TCA cycle) in macrophages 39 , and alter oxidative metabolism in other cells 61 , IFNα overexpression did not change metabolic signatures at early timepoints. However, there was an inverse relationship between the IGS and metabolic defects after LN onset, when the IGS recurred.…”
Section: Discussionmentioning
confidence: 92%
“…The IFN gene signature (IGS), a known hallmark of lupus 33 , 34 and lupus-affected tissues 35 , has been implicated in metabolic alteration of MCs 36 39 . To determine the functional relationship between IFN stimulation and metabolic alteration, we examined metabolic gene expression longitudinally in the IFNα-accelerated NZB/W murine model of LN, where the IGS increases at early timepoints following injection of IFNα adenovirus and then increases again when kidney disease develops (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GO analysis identified the expected terms for interferon responses and, also interestingly, metabolic changes in catabolism. While caution should be borne in interpreting the directionality of biological pathways based solely on gene ontology terms, we note that IFNα and viral infection have been found to generally induce a catabolic state in various cell types including macrophages [66][67][68]. Deficiencies in microglial autophagy have also been recently linked to impaired synaptic pruning and autism-like behavioural defects [17].…”
Section: Discussionmentioning
confidence: 92%